Penerapan Digital Marketing dalam Upaya Peningkatan Pendapatan Usaha Mirko Kecil dan Menengah - Jasri -; Nadia Arfan; Hasanuddin; Hurriah Ali Hasan (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
The use of the internet every day has increased. This is something that must be realized by micro, small and medium enterprises (MSMEs). One of the marketing media that is currently in great demand by SMEs to support sales promotions is digital marketing. This progress is considered very useful as a business marketing strategy that is also carried out by MSMEs. The use of E-business, E-commerce, social media, social chat and even advertising really supports MSMEs in promotion, marketing and sales. The purpose of this study is to identify the business income obtained by MSMEs in Makassar City after using digital marketing. This research method uses a quantitative approach, where data collection is done by distributing questionnaires through google form. The data was processed using the SPSS 22 application. The results of this study found that digital marketing significantly affects the income of MSME actors in Makassar City. This finding illustrates to micro, small and medium enterprises (MSMEs) that the use of digital media is very effective in running a business.